PENENTUAN KADAR NITROGEN DIOKSIDA (NO2) DALAM UDARA AMBIEN DENGAN METODE GRIESS SALTZMAN MENGGUNAKAN SPEKTROFOTOMETER - Futeri, Renny; Armin, M. Ikhlas; Samah, Selfa Dewati; Putri, Gustiarini Rika; Elisma, Netri; Syafrinal, Syafrinal; Putri, Melysa; Santia, Anisa Dwi (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2023)
Nitrogen dioxide (NO2) contributes greatly as a precursor to a number of harmful secondary air pollutants including nitric acid, the nitrate portion of secondary inorganic aerosols and oxidants including ozone. Nitrogen dioxide gas (NO2) is an ambient air pollutant along with the element nitrogen monoxide (NO) which is usually produced from human activities such as burning vehicle engine fuel, burning rubbish, burning coal and industry. This research aims to monitor the quality of air pollution in industrial areas in East Jakarta. The NO2 content in the air can be determined using the UV-Vis spectrophotometer method based on SNI 7119-2: 2017. The principle of NO2 testing uses a UV-Vis spectrophotometer based on SNI 7119-2: 2017. From the results of the tests carried out, it can be concluded that the NO2 level obtained in sample 1 was found to be 25,153 µg/Nm3, in sample 2 the NO2 level was 28,371 µg/Nm3, in sample 3 the NO2 level was 107,022 µg/Nm3, in sample 4 the NO2 level was 29,720 µg/Nm3. Nm3, and in sample 5 the NO2 level was 83.446 µg/Nm3. Based on PP RI No. 22 attachment VII of 2021 concerning air pollution control, the quality standard for NO2 is 200 µg/Nm3 for 1 hour. So it can be concluded from the results of the tests that have been carried out that the NO2 levels in the environment are still below the quality standard, which means that it is not a source of NO2 pollution, is safe and meets the requirements for human health and the environment.